An Empirical Analysis of Policy Instruments Influencing Economic Growth and Price Stability in Low-Income Nations - Yusro Hakimah (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Low-income nations face significant challenges in achieving economic growth and price stability due to limited institutional capacity, external shocks, and high poverty rates. This study aims to explore how fiscal, monetary, trade, and regulatory policies influence these dual objectives in such contexts. Using a qualitative approach through a systematic literature review, the research synthesizes findings from peer-reviewed journals, books, and reports spanning the last two decades. The analysis reveals that fiscal policies focused on infrastructure and human capital development drive economic growth, as seen in countries like Ethiopia and Rwanda, but require careful management to avoid inflationary pressures. Monetary policies stabilize prices through interest rate adjustments, yet tight measures can hinder investment in resource-constrained settings. Trade policies enhance growth by fostering market integration, though reliance on commodity exports risks price volatility. Strong governance is critical for effective policy implementation, while external dependencies limit autonomy. The study concludes that coordinated, context-specific policies are essential for balancing growth and stability. Policymakers should prioritize institutional reforms and adaptive strategies to enhance resilience and promote sustainable development in low-income nations.